PEMBERDAYAAN SEKTOR INFORMAL (Suatu Alternatif Pembangunan Ekonomi Rakyat) - Kausar Kausar (JIP ( Jurnal Industri dan Perkotaan ), 2011)
This paper aims to look at the empowerment of the informal sector as an alternative to the economic development. Many problems faced by Indonesian people associated with the policy of economic regulation, especially the prices always go up and not affordable by the community. Thus, alternative economic development of the people become a rational choice to always be developed.